EVALUATION OF THE MAIN RESULTS OF THE DEVELOPMENT OF ELECTRIC POWER INDUSTRY OF RUSSIA FOR 2015 - N. Lyubimova (Publishing House of the State University of Management, 2016)
The 2015 economic crisis in Russia has slowed, but the drop is not completely stopped, which is reflected in the results of the power industry. In 2015, compared with 2014 power consumption continued to decline, as in Russia as a whole, and in terms of centralized power. Decreased the maximum load. At the same time, there have been positive trends: capacities update, the number of accidents has decreased, network losses were reduced, the wholesale market of electric power and capacity has been further developed. However, the introduction of new capacities has led, on the one hand, to improve the reliability of power supply, and on the other, an increase in the cost of electricity and, consequently, to nonpayment.